Evaluating Food Security: The Interplay of Income Sources for Pepper Farmers in West Kalimantan - Paulina, Yohana; Yurisinthae, Erlinda; Kurniasih, Dewi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
Food security is a key global challenge, with agriculture playing a crucial role in ensuring food availability, access, and stability. Farming families, especially in remote border areas, often face poverty and unmet nutritional needs, making them vulnerable to food insecurity. Factors like poor infrastructure and high food prices exacerbate the situation in these regions. Pepper farming is a vital income source for farmers in West Kalimantan's border areas. This study analyzes pepper farming income and its impact on food security using descriptive and logistic regression methods. This study aims to analyze the income structure of pepper farmers and its relationship with food security by employing descriptive statistics and logistic regression methods. Findings reveal that pepper farmers derive income from three primary sources: on-farm, off-farm, and non-farm activities, with an average annual farming income of IDR 48,331,800. The study classified most pepper farmers as